2015
DOI: 10.1021/acsami.5b05933
|View full text |Cite
|
Sign up to set email alerts
|

Syndiotactic Polystyrene/Hybrid Silica Spheres of POSS Siloxane Composites Exhibiting Ultralow Dielectric Constant

Abstract: Homogeneously dispersed hybrid silica/syndiotactic polystyrene composites were investigated for low-κ dielectric applications. The composites were prepared by a solution blending method, and their microstructures were analyzed by SEM, TEM, and AFM. Crystallization and phase transformation behavior of sPS were investigated using differential scanning calorimetry and wide-angle X-ray diffraction. These composites exhibited improved thermal stability and reduced thermal expansion coefficients. Promising dielectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 50 publications
(120 reference statements)
0
67
0
Order By: Relevance
“…The FTIR results are in good agreement with the X‐ray diffraction results. It has been reported that the addition of inorganic nanofillers can influence the polymorphism of sPS . For example, carbon nanotubes, hybrid silica spheres and modified layered silicates stabilize the thermodynamically stable β form over the α form .…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR results are in good agreement with the X‐ray diffraction results. It has been reported that the addition of inorganic nanofillers can influence the polymorphism of sPS . For example, carbon nanotubes, hybrid silica spheres and modified layered silicates stabilize the thermodynamically stable β form over the α form .…”
Section: Resultsmentioning
confidence: 99%
“…The hybrid silica facilitates the formation of thermodynamically stable β crystalline, which reduces the dielectric constant and loss of sPS to 1.95 and 1 × 10 −4 at 5 GHz, respectively. [85]…”
Section: Thermoplastic Resinsmentioning
confidence: 99%
“…Since PS is brittle and soften at relatively low temperature, the need of making composites for achieving the characteristics requested for a specific usage. Among the different PS composites [ 6 , 7 , 8 , 9 ], in the last two decades, increasing attention has been paid to those designed and realized by using polyhedral oligomeric silsesquioxanes (POSSs) [ 10 , 11 , 12 ]. Historically a lot of studies and application focused on those materials characterized by the R 2 SiO unit, inorganic silica and/or organic silicones, but more recently silsesquioxanes bearing general composition of RSiO 3/2 gained growing interest [ 13 ].…”
Section: Introductionmentioning
confidence: 99%